Landscape and Health in Sustainable Development - Bernat, Sebastian (Problemy Ekorozwoju, 2019)
The article discusses the correlations between health, landscape, and sustainable development. In the first part, the basic concepts are defined. Attention is drawn to the therapeutic effect of landscape, and the subject of therapeutic parks and gardens is discussed. Based on the conducted analyses, characteristics of landscape with therapeutic properties are proposed, and the practical application of research on the landscape-health relationship is indicated. Perception is identified as the key to understanding the therapeutic properties of landscape. Taking care of the therapeutic values of landscape should be part of sustainable development.